Microbiota in Human Periodontal Abscess Revealed by 16S rDNA Sequencing - Chen, Jiazhen; Wu, Xingwen; Zhu, Danting; Xu, Meng; Yu, Youcheng; Yu, Liying; Zhang, Wenhong (Frontiers in Microbiology, 2019)
Periodontal abscess is an oral infective emergency caused by various kinds of bacteria. We aimed to characterize the microbiota composition in periodontal abscess by metagenomic method and compare it with the corresponding pocket and healthy gingival crevice to investigate the specific bacteria associated with periodontal abscess. Samples from abscess pus (AB), periodontal pocket coronally above the abscess (PO), and gingival crevice of periodontal healthy tooth were obtained from 20 periodontal abscess patients. Furthermore, healthy gingival crevice samples were obtained from 25 healthy individuals. Bacterial DNA was extracted and 16S rRNA gene metagenomic was sequenced to characterize the microbiota and determine taxonomic classification. The beta-diversity analysis results showed that the AB and PO groups have similar composition. Porphyromonas gingivalis, Prevotella nigrescens, Prevotella intermedia, Fusobacterium spp., and other Prevotella spp. were the predominant bacteria in human periodontal abscesses. The abundance of Filifactor alocis and Atopobium rimae was significantly higher in periodontal abscesses than in the periodontal pocket, suggesting their association with periodontal abscess formation. In conclusion, we characterized the microbiota in periodontal abscess and showed that F. alocis and A. rimae were positive-associated with abscess formation though the bacterial abundance and diversity in periodontal abscess and pocket were highly similar. That gives us a good understanding in the component of the periodontal abscess and does help in antibiotic therapy.